A high-strength high-plasticity cast austenitic stainless steel support industrial preparation method
Patent Information
- Application Number
- CN202611178495.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-05
AI Technical Summary
常规铸造时,为了追求强度,往往会产生粗大的枝晶和网状δ铁素体,导致塑性很难超过35%,若想提高塑性,必须大幅牺牲强度,存在塑性超过35%,但强度低于要求值
[0005]与现有技术相比,本发明的有益效果为:(1)本发明通过AOD精炼与稀土包芯线喂丝变质处理将有害杂质硫控制在≤0.005%,并生成弥散稀土硫化物,裂纹扩展时需绕过这些弥散球状颗粒,路径曲折,消耗更多能量,同时细小弥散的δ铁素体枝晶作为韧性第二相,在裂纹尖端发生塑性变形,吸收裂纹扩展能,断裂前产生显著塑性颈缩,先弯后断,实现了从脆性穿晶断裂向韧性微孔聚集型断裂的模式转变,实现强塑性同步提升,在意外超载时先弯曲后断裂,为设备巡检提供肉眼可见的机械式预警信号,杜绝突发性灾难;(2)通过机械共振振动浇注与强制风冷凝固在凝固期利用振动剪切力打碎δ枝晶,使δ铁素体呈晶状,细小弥散球状稀土硫化物与δ铁素体枝晶均匀分布,消除了宏观硬度差,切削力波动极小,且稀土硫化物本身具有固体润滑效应,在刀尖形成转移润滑膜,降低摩擦系数,超细晶组织使切屑呈短螺旋状,排屑顺畅,减少二次切削磨损,提升丝锥寿命,同时降低加工表面粗糙度,省去后续打磨抛光工序;(3)稀土占据晶界高能位点,将Cr23C6的形核驱动力降至最低,消除了形核热力学条件;超低碳和稀土Cottrell气团钉扎效应降低了碳的扩散系数,使碳原子无法在焊接急冷过程中长程迁移至晶界;焊接热循环本身对热影响区相当于一次原位二次固溶,已溶解的碳化物在冷却时因缺乏形核基底而无法重新析出,耐晶间腐蚀性能与固溶态母材无统计学差异;(4)机械振动在固液两相区施加剪切应力,迫使枝晶间残留液相产生强迫对流,破碎的枝晶碎片被冲刷至缩松区域充当异质形核基底,加速局部凝固并堵塞补缩通道末端,强制风冷提高了整体冷却速率,凝固时间缩短,收缩总量减小,振动产生的压力波动辅助钢水向枝晶间微区渗透补缩,从根源上消除了显微缩松的生成条件,保证气密性良好;(5)采用双级连续固溶热处理与水雾淬火,950℃低温预固溶完成碳化物溶解和合金元素均匀化,1080℃×15min高温瞬态固溶利用时间-温度补偿原理,仅使晶粒发生亚晶界多边形化、位错重新排列,而不发生再结晶长大的临界时间窗口,保留了细晶强化效果;水雾+压缩空气混合淬火消除了蒸汽膜阶段,热通量均匀且冲击力远小于水淬,铸件各部位同步冷却,热应力自平衡,平面度高;(6)采用铈盐-柠檬酸无铬钝化,六价铬阴性,铈盐(Ce3+)在双氧水氧化环境下水解生成富铈氢氧化物/氧化物的复合钝化膜,膜层致密且自修复性强,且不引入任何Cr6+源,钝化液经中和、沉淀后可排放,无需后续脱铬处理。
Smart Images

Figure CN122669288B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of steel material preparation technology, and in particular to an industrial method for preparing a high-strength, high-plasticity cast austenitic stainless steel support. Background Technology
[0002] Cast austenitic stainless steel is widely used in the manufacture of various structural load-bearing supports, pump bodies, valves, and pipe fittings due to its excellent corrosion resistance and good comprehensive mechanical properties. During conventional casting, in pursuit of strength, coarse dendrites and network δ-ferrite are often produced, making it difficult to exceed 35% plasticity. To improve plasticity, strength must be significantly sacrificed, resulting in plasticity exceeding 35% but strength below the required value. Summary of the Invention
[0003] The purpose of this invention is to address the shortcomings of existing technologies by proposing an industrial method for preparing high-strength, high-plasticity cast austenitic stainless steel supports.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: an industrial preparation method for a high-strength, high-ductility cast austenitic stainless steel bracket, comprising the following steps: S1: AOD refining of molten steel and rare earth cored wire feeding modification treatment; S11: Scrap steel, ferrochrome, ferronickel, and other raw materials are melted into molten steel in a medium-frequency induction furnace; Furthermore, the temperature in the medium-frequency induction furnace is ≥1600℃; S12: The molten steel is transferred to the AOD argon-oxygen refining furnace for blowing, and the argon-oxygen ratio is controlled to decarburize, desulfurize, and deoxidize the molten steel, thereby reducing the carbon content of the molten steel. Furthermore, the refining process includes the following sub-steps: S121: In the AOD argon-oxygen refining furnace, O2:Ar = 3:1~4:1 is blown in, with oxygen as the main component. High-pressure oxygen is blown in simultaneously through the top and side lances. The temperature of the molten steel rises to 1650℃~1700℃. The carbon content is high, and oxygen preferentially reacts with carbon. CO is burned to produce CO2, and a large amount of brown smoke is produced at the furnace mouth. The exhaust gas analyzer shows that the CO content in the exhaust gas drops sharply, and when the temperature of the molten steel reaches its peak, the carbon content drops to 0.40%~0.50%. S122: Gradually adjust the side-blown gas ratio to O2:Ar=1:1~1:2, significantly increase the argon flow rate. The large injection of argon forms a large number of tiny bubbles inside the molten steel. When the bubbles are first generated, there is no CO. The bubbles compete for dissolved carbon and oxygen in the molten steel, promoting the reaction to move to the right. The temperature of the molten steel is maintained at 1700℃~1720℃. The exhaust gas analyzer shows that the CO partial pressure continues to decrease and the carbon content exceeds the critical point of 0.10%. S123: Switch the argon-oxygen ratio to O2:Ar=1:3~1:4, with argon as the main gas and oxygen only in trace amounts. The large amount of argon gas strongly stirs the molten steel, generating a vacuum suction effect. This draws in the trace amounts of carbon and oxygen remaining in the molten steel, which combine to form CO and are then expelled. At the same time, Cr2O3 in the slag is also reduced by the carbon in the molten steel: Cr2O3 + 3C → 2Cr + 3CO, further squeezing out the residual carbon. The temperature of the molten steel is maintained at 1720℃~1750℃, and the high argon gas stirring is maintained for 10~15 minutes, during which the carbon content is stably reduced to 0.03%~0.05%. S124: In steps S122-S123, ferrosilicon or aluminum particles are added in batches. The exothermic oxidation Si+O2→SiO2 is used to pull the temperature of the molten steel back to above 1700℃, providing energy for the decarburization reaction. S125: In steps S121-S123, active lime is added to the furnace in batches to control the slag basicity at 2.0~2.5. The high basicity slag adsorbs the SiO2 generated by decarburization and absorbs the sulfur in the molten steel. S13: Use a wire feeder to feed a mixed rare earth cored wire of cerium (Ce) and lanthanum (La) into the depth of the molten steel at a set speed; Furthermore, the wire feeding rate is 0.15% to 0.25% of the weight of the molten steel; Furthermore, the wire feeding speed is 2.5~3.0 m / s; S14: After feeding the wire, let it stand for several minutes to allow the rare earth elements to react fully, and then remove the residue; Furthermore, let it stand for 5-8 minutes after feeding the silk; Furthermore, the tapping temperature of the molten steel after step S1 is 1580±10℃. S2: Prepare the heat storage mold shell; S21: Topcoat application and drying; S211: Preparation of surface layer slurry; Using silica sol as a binder, zircon powder is slowly added to silica sol at a ratio of zircon powder: silica sol = 3.2:1~4.0:1. At the same time, 0.2% of the coating mass of wetting agent and 0.2% of defoamer are added. After stirring continuously for 2~3 hours, the slurry density is 2.7~2.8 g / mL and the flow cup viscosity is 32±1 seconds. Furthermore, the wetting agent is polyoxyethylene alkyl ether, and the defoamer is n-octanol; S212: Immerse the wax model assembly in the surface slurry prepared in step S211; S213: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up the surface. S214: Send the module coated with slurry into the sand-spraying machine and evenly sprinkle 80~120 mesh zircon sand on it; S215: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 50%~70%, dry for 14 hours; S216: Repeat steps S212-S215, applying two coats of topcoat; S22: Back coating and drying; S221: Preparation of backing slurry; Using silica sol as a binder, 200-mesh mullite powder was added, with a mullite powder: silica sol ratio of 1.8:1 to 1.9:1. The mixture was stirred for 2 to 3 hours and set aside. The slurry density was 1.81 to 1.83 g / mL and the viscosity was 13 ± 1 second. S222: Immerse the module in pure silica sol for 2-3 seconds and then remove it to wet the surface of the previous layer. S223: Immerse the wax mold assembly in the backing slurry prepared in step S221; S224: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up the surface. S225: The module coated with slurry is sent into the sand-spraying machine and evenly sprinkled with 16~30 mesh mullite sand; S226: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 35%~50%, dry for 12~18 hours; S227: Repeat steps S223-S227, applying 3-4 layers of back coat; S23: Sealing layer and drying; S231: The sealant grout has the same formula as the backing grout. S232: Immerse the wax mold assembly into the sealing slurry prepared in step S231; S233: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up. S234: Transfer to a constant temperature and humidity drying chamber, with conditions of temperature 22~24℃ and humidity 35%~50%, and dry for 8~12 hours; S24: Dewaxing and roasting; S241: Before dewaxing, perform a pressure test on the dewaxing kettle and preheat it 1-2 times. Place the mold pouring cup upside down on the dewaxing trolley and quickly feed it into the dewaxing kettle. Immediately close the machine door, open the steam valve, and quickly raise the pressure to 0.6-0.75MPa. Hold the pressure at 0.6-0.75MPa and 135℃-160℃ for 6-15 minutes. After the holding time is up, close the steam valve and slowly release the steam. After the pressure gauge returns to zero, open the kettle door and pull out the mold shell. S242: Place the dewaxed mold shell into the firing furnace, start the firing furnace, and heat it to 1000~1050℃ according to the set program. The heating rate is controlled at 5~8℃ / min to avoid thermal shock cracking of the mold shell due to excessive heating. Hold it at 1000~1050℃ for 1.5~2 hours. After the holding time is over, open the furnace door and take out the mold shell. After firing, the temperature of the mold shell is maintained at 700~800℃. S3: Molten steel is poured through mechanical resonance vibration and then solidified by forced air cooling to form a casting; S31: With the pouring cup of the baked high-temperature mold shell facing vertically upwards, quickly hoist it onto the pneumatic / eccentric wheel mechanical vibration table and fix it securely; S32: Slowly tilt the ladle to allow the refined molten steel from step S1 to flow into the mold shell in a spiral shape along the inner wall of the pouring cup, with the pouring time controlled within the set time. S33: Immediately after the molten steel is poured, start the vibrating table and set the frequency and amplitude; S34: After casting, the temperature of the molten steel decreases and it enters the solid-liquid two-phase region where δ ferrite begins to precipitate. Mechanical shearing force is used to break up the growing primary δ dendrites, forming a large number of free crystal nuclei. Vibration continues for several minutes until the outer shell is completely solidified. Furthermore, the temperature of the molten steel in the solid-liquid two-phase region is 1380℃~1420℃; S35: After casting is completed, the array-type axial flow fan around the mold shell is turned on to provide high-flow forced air convection cooling to the surface of the mold shell until the surface temperature of the mold shell drops below 600℃. Furthermore, the air velocity for high-flow forced air convection cooling is ≥10m / s; S36: When the outer shell of the mold is completely solidified and the reading of the vibrating table ammeter drops significantly, stop the vibrating table. After stopping the machine, loosen the clamping device and transfer the mold along with the vibrating table surface to the cooling rack for continued natural air cooling or auxiliary air cooling to below 200°C. Furthermore, if the color of the mold shell surface changes from bright red to dark red, the outer shell of the mold shell is completely solidified; if the reading of the vibration table ammeter drops significantly, it indicates that the molten steel has solidified and no longer consumes vibration energy. S4: Cleaning, cutting and grinding castings; S41: After the casting has cooled naturally to below 200°C in the mold shell, mechanical vibration or water blasting is performed to remove the outer mullite shell layer. S42: Use an oxyacetylene flame cutter or band saw to separate the support block from the gating system; S43: Use an angle grinder or shot blasting machine to remove residual shell, flash, and oxide scale from the surface of the bracket to expose the metal. S5: The bracket undergoes two-stage continuous solution heat treatment and water mist quenching; S51: After cleaning, cutting and grinding the bracket in step S4, blow the surface and inner cavity with compressed air to remove residual molding sand, iron filings and oxide scale, and wipe the oil stains on the surface of the casting with industrial alcohol or acetone. Furthermore, the compressed air pressure is ≥0.6 MPa; S52: Place the cleaned supports evenly on the bottom bricks at the feed end of the walking beam furnace, leaving gaps between the castings to ensure uniform hot air circulation; S53: Start the stepper beam drive system and feed the supports into the furnace zone one batch by batch according to the set cycle. The furnace temperature is controlled at 950±5℃ and held for 2±0.5 hours to fully dissolve the grain boundary carbides and uniformly alloy the elements. Furthermore, the cycle is set to 5-10 minutes per step cycle; S54: The walking beam pushes the casting to the transition section, and the roller conveyor is used for rapid transfer to ensure that it enters the second zone of the furnace from the first zone within 3 minutes. S55: The support enters the second zone of the furnace, and the furnace temperature is controlled at 1080±5℃ for 15±1 minutes. S56: The walking beam quickly sends the support after the heat preservation in Zone 2 of the furnace into the quenching zone. After the support comes out of the furnace, it immediately enters the high-pressure water mist and compressed air mixed spray zone until the surface temperature of the casting drops below 200°C. Furthermore, the water mist pressure in the high-pressure water mist and compressed air mixing and spraying zone is 0.6~0.8MPa, the air pressure is 0.5~0.6MPa, and the cooling rate is ≥50℃ / s; S57: After the bracket leaves the spray zone, it enters the natural air drying section or the compressed air blowing section to blow away the residual water stains on the surface. The bracket continues to move forward with the roller conveyor and cools naturally to room temperature in the air. Furthermore, the furnace atmosphere is either a slightly oxidizing atmosphere or protected by argon. Furthermore, in step S5, the walking beam continuous furnace is replaced with two box-type resistance furnaces. One box-type resistance furnace is set at 950°C and the other at 1080°C. The transfer time between the two furnaces is controlled within 3 minutes, and the water mist quenching station is set at a distance of ≤1 meter from the outlet of the high-temperature furnace. S6: Chromium-free passivation of the support; S61: The bracket treated in step S5 is completely immersed in the pickling tank at room temperature for several minutes to remove the heat-treated oxide scale. Furthermore, if the stent still has residual dark brown oxide scale after step S61, it can be acid-washed for 3-5 minutes. Furthermore, the solution in the pickling tank is 10% sulfuric acid + 5% hydrofluoric acid. The preparation method is as follows: first add tap water to the pickling tank to fill about 2 / 3 of the tank volume, then slowly add 98% concentrated sulfuric acid to a final concentration of 10%, and then slowly add 40% hydrofluoric acid to a final concentration of 5%. S62: Immerse the bracket in the first tap water rinsing tank, lift and shake it up and down to fully dilute and rinse away the acid residue on the surface of the bracket, then transfer the bracket into the second tap water rinsing tank and repeat the up and down lifting and shaking cleaning. Furthermore, the total time for rinsing with tap water twice is 2-3 minutes; S63: Heat the passivation solution to 40~50℃ and keep it at a constant temperature. Immerse the drained support after washing in water completely into the passivation tank and soak for several minutes. Furthermore, the passivation solution formula is 5~8g / L citric acid + 30~50ml / L hydrogen peroxide + 0.5~1g / L cerium nitrate. The pH of the passivation solution is adjusted to 1.5~2.5 with ammonia. The preparation method is as follows: add deionized water to about 2 / 3 of the passivation tank volume; add citric acid at a concentration of 5~8g / L and stir until completely dissolved; add cerium nitrate at a concentration of 0.5~1g / L and stir until completely dissolved; then add 30% hydrogen peroxide at a concentration of 30~50ml / L and stir evenly; slowly add ammonia dropwise to adjust the pH of the passivation solution to 1.5~2.5. Furthermore, after treating 2-3 batches of stents with the passivation solution, add 3-5 ml / L of hydrogen peroxide according to the consumption to maintain an effective concentration; S64: Immerse the passivated support in deionized water, lift and shake it several times and soak it for several minutes. Then, lift out the cleaned support, let it stand to drain, and then dry it with hot air to obtain the finished support. Furthermore, the conductivity of deionized water is ≤5μS / cm; Furthermore, the drying temperature is ≤80℃.
[0005] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention controls the harmful impurity sulfur to ≤0.005% through AOD refining and rare earth cored wire feeding modification treatment, and generates dispersed rare earth sulfides. When the crack propagates, it needs to bypass these dispersed spherical particles, the path is tortuous, and more energy is consumed. At the same time, the fine dispersed δ ferrite dendrites, as the tough second phase, undergo plastic deformation at the crack tip, absorb the crack propagation energy, and produce significant plastic necking before fracture. It bends first and then breaks, realizing the transformation from brittle transgranular fracture to tough microporous aggregate fracture mode, realizing the simultaneous improvement of strong plasticity. In case of accidental overload, it bends first and then breaks, providing a meat for equipment inspection. (1) Visible mechanical early warning signals prevent sudden disasters; (2) Through mechanical resonance vibration casting and forced air cooling solidification, the δ dendrites are broken by vibration shear force during the solidification period, so that the δ ferrite is crystallized. The fine and dispersed spherical rare earth sulfides and δ ferrite dendrites are evenly distributed, eliminating the macroscopic hardness difference, the cutting force fluctuation is minimal, and the rare earth sulfides themselves have a solid lubrication effect, forming a transfer lubrication film at the tip of the tool, reducing the friction coefficient. The ultra-fine grain structure makes the chips short spiral, the chip removal is smooth, the secondary cutting wear is reduced, the tap life is improved, and the surface roughness of the machining is reduced, eliminating the need for subsequent grinding and polishing processes; (3) Rare earth occupies the high-energy sites of the grain boundary, making Cr 23 The nucleation driving force of C6 is reduced to the minimum, eliminating the nucleation thermodynamic conditions; the ultra-low carbon and rare earth Cottrell piling effect reduces the carbon diffusion coefficient, preventing carbon atoms from migrating long distances to the grain boundaries during welding quenching; the welding thermal cycle itself is equivalent to a first in-situ secondary solid solution in the heat-affected zone, and the dissolved carbides cannot be re-precipitated during cooling due to the lack of a nucleation substrate, and the intergranular corrosion resistance is not statistically different from that of the solid solution base material; (4) Mechanical vibration applies shear stress to the solid-liquid two-phase region, forcing the residual liquid phase between dendrites to generate forced convection, and the broken dendrite fragments are washed to the shrinkage porosity area to act as a heterogeneous nucleation substrate, accelerating local solidification and blocking the end of the shrinkage channel. Forced air cooling increases the overall cooling rate, shortens the solidification time, and reduces the total shrinkage. The pressure fluctuations generated assist the molten steel to penetrate and replenish the interdendritic micro-regions, eliminating the conditions for the formation of micro-shrinkage porosity from the root and ensuring good air tightness; (5) adopting a two-stage continuous solution heat treatment and water mist quenching, 950℃ low-temperature pre-solidification to complete the dissolution of carbides and homogenization of alloy elements, 1080℃×15min high-temperature transient solution utilizes the time-temperature compensation principle to only cause subgrain boundary polygonization and dislocation rearrangement, without the critical time window of recrystallization growth, thus preserving the fine grain strengthening effect; water mist + compressed air mixed quenching eliminates the steam film stage, the heat flux is uniform and the impact force is much smaller than water quenching, all parts of the casting are cooled synchronously, the thermal stress is self-balanced, and the flatness is high; (6) adopting cerium salt-citric acid chromium-free passivation, hexavalent chromium anion, cerium salt (Ce 3+A cerium-rich hydroxide / oxide composite passivation film is generated by hydrolysis under hydrogen peroxide oxidation. The film is dense and has strong self-healing properties, and does not introduce any Cr. 6+ The passivation solution can be discharged after neutralization and precipitation, without the need for subsequent chromium removal treatment. Attached Figure Description
[0006] Figure 1 This is a flowchart of the industrial preparation method of the high-strength, high-plasticity cast austenitic stainless steel bracket of the present invention.
[0007] Figure 2 The image shows a 100X image of the metallographic structure of the high-strength, high-plasticity cast austenitic stainless steel support of the present invention after corrosion.
[0008] Figure 3 The image shows a 500X image of the metallographic structure of the high-strength, high-plasticity cast austenitic stainless steel bracket of the present invention after corrosion. Detailed Implementation
[0009] To provide a further understanding of the purpose, structure, features, and functions of the present invention, detailed descriptions are provided below with reference to specific embodiments.
[0010] Please refer to the reference. Figure 1 This invention provides an industrial method for preparing a high-strength, high-ductility cast austenitic stainless steel support, comprising the following steps: S1: AOD refining of molten steel and rare earth cored wire feeding modification treatment; S11: Scrap steel, ferrochrome, ferronickel, and other raw materials are melted into molten steel in a medium-frequency induction furnace; Furthermore, the temperature in the medium-frequency induction furnace is ≥1600℃; S12: The molten steel is transferred to the AOD argon-oxygen refining furnace for blowing, and the argon-oxygen ratio is controlled to decarburize, desulfurize and deoxidize the molten steel, reducing the carbon content of the molten steel to below 0.05%. Furthermore, the refining process includes the following sub-steps: S121: In the AOD argon-oxygen refining furnace, O2:Ar = 3:1~4:1 is blown in, with oxygen as the main component. High-pressure oxygen is blown in simultaneously through the top and side lances. The temperature of the molten steel rises to 1650℃~1700℃. The carbon content is high, and oxygen preferentially reacts with carbon. CO is burned to produce CO2, and a large amount of brown smoke is produced at the furnace mouth. The exhaust gas analyzer shows that the CO content in the exhaust gas drops sharply, and when the temperature of the molten steel reaches its peak, the carbon content drops to 0.40%~0.50%. S122: Gradually adjust the side-blown gas ratio to O2:Ar=1:1~1:2, significantly increase the argon flow rate. The large injection of argon forms a large number of tiny bubbles inside the molten steel. When the bubbles are first generated, there is no CO. The bubbles compete for dissolved carbon and oxygen in the molten steel, promoting the reaction to move to the right. The temperature of the molten steel is maintained at 1700℃~1720℃. The exhaust gas analyzer shows that the CO partial pressure continues to decrease and the carbon content exceeds the critical point of 0.10%. S123: Switch the argon-oxygen ratio to O2:Ar=1:3~1:4, with argon as the main gas and oxygen only in trace amounts. The large amount of argon gas strongly stirs the molten steel, generating a vacuum suction effect. This draws in the trace amounts of carbon and oxygen remaining in the molten steel, which combine to form CO and are then expelled. At the same time, Cr2O3 in the slag is also reduced by the carbon in the molten steel: Cr2O3 + 3C → 2Cr + 3CO, further squeezing out the residual carbon. The temperature of the molten steel is maintained at 1720℃~1750℃, and the high argon gas stirring is maintained for 10~15 minutes, during which the carbon content is stably reduced to 0.03%~0.05%. S124: In steps S122-S123, ferrosilicon or aluminum particles are added in batches. The exothermic oxidation Si+O2→SiO2 is used to pull the temperature of the molten steel back to above 1700℃, providing energy for the decarburization reaction. S125: In steps S121-S123, active lime is added to the furnace in batches to control the slag basicity at 2.0~2.5. The high basicity slag adsorbs the SiO2 generated by decarburization and absorbs the sulfur in the molten steel. S13: Use a wire feeder to feed a mixed rare earth cored wire of cerium (Ce) and lanthanum (La) into the depth of the molten steel at a set speed; Furthermore, the wire feeding rate is 0.15% to 0.25% of the weight of the molten steel; Furthermore, the wire feeding speed is 2.5~3.0 m / s; S14: After feeding the wire, let it stand for several minutes to allow the rare earth elements to react fully, and then remove the residue; Furthermore, let it stand for 5-8 minutes after feeding the silk; Furthermore, the tapping temperature of the molten steel after step S1 is 1580±10℃. AOD refining and rare earth cored wire feeding modification treatment control harmful sulfur impurities to ≤0.005% and generate dispersed rare earth sulfides to purify the grain boundaries.
[0011] S2: Prepare the heat storage mold shell; S21: Topcoat application and drying; S211: Preparation of surface layer slurry; Using silica sol as a binder, zircon powder is slowly added to silica sol at a ratio of zircon powder: silica sol = 3.2:1~4.0:1. At the same time, 0.2% of the coating mass of wetting agent and 0.2% of defoamer are added. After stirring continuously for 2~3 hours, the slurry density is 2.7~2.8 g / mL and the flow cup viscosity is 32±1 seconds. Furthermore, the wetting agent is polyoxyethylene alkyl ether, and the defoamer is n-octanol; S212: Immerse the wax model assembly in the surface slurry prepared in step S211 for about 20 to 30 seconds. S213: Remove the module, slowly rotate and tilt for 1-3 minutes to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up. S214: Send the module coated with slurry into the sand-spraying machine and evenly sprinkle 80~120 mesh zircon sand on it; S215: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 50%~70%, dry for 14 hours; S216: Repeat steps S212-S215, applying two coats of topcoat; S22: Back coating and drying; S221: Preparation of backing slurry; Using silica sol as a binder, 200-mesh mullite powder was added, with a mullite powder: silica sol ratio of 1.8:1 to 1.9:1. The mixture was stirred for 2 to 3 hours and set aside. The slurry density was 1.81 to 1.83 g / mL and the viscosity was 13 ± 1 second. S222: Immerse the module in pure silica sol for 2-3 seconds and then remove it to wet the surface of the previous layer. S223: Immerse the wax model assembly in the back layer slurry prepared in step S221 for about 20 to 30 seconds. S224: Remove the module, slowly rotate and tilt for 1-3 minutes to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up. S225: The module coated with slurry is sent into the sand-spraying machine and evenly sprinkled with 16~30 mesh mullite sand; S226: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 35%~50%, dry for 12~18 hours; S227: Repeat steps S223-S227, applying 3-4 layers of back coat; S23: Sealing layer and drying; S231: The sealant grout has the same formula as the backing grout. S232: Immerse the wax mold assembly in the sealing slurry prepared in step S231 for about 20 to 30 seconds; S233: Remove the module, slowly rotate and tilt for 1-3 minutes to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up. S234: Transfer to a constant temperature and humidity drying chamber, with conditions of temperature 22~24℃ and humidity 35%~50%, and dry for 8~12 hours; S24: Dewaxing and roasting; S241: Before dewaxing, perform a pressure test on the dewaxing kettle and preheat it 1-2 times. Place the mold pouring cup upside down on the dewaxing trolley and quickly feed it into the dewaxing kettle. Immediately close the machine door, open the steam valve, and quickly raise the pressure to 0.6-0.75MPa. Hold the pressure at 0.6-0.75MPa and 135℃-160℃ for 6-15 minutes. After the holding time is up, close the steam valve and slowly release the steam. After the pressure gauge returns to zero, open the kettle door and pull out the mold shell. S242: Place the dewaxed mold shell into the firing furnace, start the firing furnace, and heat it to 1000~1050℃ according to the set program. The heating rate is controlled at 5~8℃ / min to avoid thermal shock cracking of the mold shell due to excessive heating. Hold it at 1000~1050℃ for 1.5~2 hours. After the holding time is over, open the furnace door and take out the mold shell. After firing, the temperature of the mold shell is maintained at 700~800℃. Manufacture a mold shell with a controllable thermal conductivity to facilitate subsequent use with air cooling to achieve directional cooling rate.
[0012] S3: Molten steel is poured through mechanical resonance vibration and then solidified by forced air cooling to form a casting; S31: With the pouring cup of the baked high-temperature mold shell facing vertically upwards, quickly hoist it onto the pneumatic / eccentric wheel mechanical vibration table and fix it securely; S32: Slowly tilt the ladle to let the refined molten steel from step S1 flow into the mold shell in a spiral shape along the inner wall of the pouring cup, and control the pouring time within 10 to 15 seconds. S33: Start the vibration table within 3 seconds after the molten steel is poured, set the frequency to 50Hz and the amplitude to ±2mm; S34: 30-60 seconds after pouring, the temperature of the molten steel naturally drops to 1380℃-1420℃, entering the solid-liquid two-phase region where δ ferrite begins to precipitate. Mechanical shearing force is used to break up the growing primary δ dendrites, forming a large number of free crystal nuclei. Vibration continues for 3-5 minutes until the outer shell is completely solidified. S35: After casting is completed, the array-type axial flow fan around the mold shell is turned on to provide high-flow forced air convection cooling to the surface of the mold shell until the surface temperature of the mold shell drops below 600℃. Furthermore, the air velocity for high-flow forced air convection cooling is ≥10m / s; S36: When the outer shell of the mold is completely solidified and the reading of the vibrating table ammeter drops significantly, stop the vibrating table. After stopping the machine, loosen the clamping device and transfer the mold along with the vibrating table surface to the cooling rack for continued natural air cooling or auxiliary air cooling to below 200°C. Furthermore, if the color of the mold shell surface changes from bright red to dark red, the outer shell of the mold shell is completely solidified; if the reading of the vibration table ammeter drops significantly, it indicates that the molten steel has solidified and no longer consumes vibration energy. Mechanical resonance vibration casting and forced air cooling are used to break up δ dendrites during the solidification period by using vibration shear force, combined with air cooling to refine the grains.
[0013] S4: Cleaning, cutting and grinding castings; S41: After the casting has cooled naturally to below 200°C in the mold shell, mechanical vibration or water blasting is performed to remove the outer mullite shell layer. S42: Use an oxyacetylene flame cutter or band saw to separate the support block from the gating system; S43: Use an angle grinder or shot blasting machine to remove residual shell, flash, and oxide scale from the surface of the bracket to expose the metal. A clean casting is obtained through shell cleaning, cutting, and polishing, in preparation for heat treatment.
[0014] S5: The bracket undergoes two-stage continuous solution heat treatment and water mist quenching; S51: After cleaning, cutting and grinding the bracket in step S4, blow the surface and inner cavity with compressed air to remove residual molding sand, iron filings and oxide scale, and wipe the oil stains on the surface of the casting with industrial alcohol or acetone. Furthermore, the compressed air pressure is ≥0.6 MPa; S52: Place the cleaned supports evenly on the bottom bricks at the feed end of the walking beam furnace, leaving a 10-20mm gap between the castings to ensure uniform hot air circulation; S53: Start the stepper beam drive system and feed the supports into the furnace zone one batch by batch according to the set cycle. The furnace temperature is controlled at 950±5℃ and held for 2.0 hours to fully dissolve the grain boundary carbides and uniformly alloy the elements. Furthermore, the cycle is set to 5-10 minutes per step cycle; S54: The walking beam pushes the casting to the transition section, and the roller conveyor is used for rapid transfer to ensure that it enters the second zone of the furnace from the first zone within 3 minutes. S55: The support enters the second zone of the furnace, and the furnace temperature is controlled at 1080±5℃ for 15±1 minutes. S56: The walking beam quickly sends the support after the heat preservation in Zone 2 of the furnace into the quenching zone. After the support comes out of the furnace, it immediately enters the high-pressure water mist and compressed air mixed spray zone, with a cooling rate of ≥50℃ / s, until the surface temperature of the casting drops below 200℃. Furthermore, the water mist pressure in the high-pressure water mist and compressed air mixing and spraying zone is 0.6~0.8MPa, and the air pressure is 0.5~0.6MPa; S57: After the bracket leaves the spray zone, it enters the natural air drying section or the compressed air blowing section to blow away the residual water stains on the surface. The bracket continues to move forward with the roller conveyor and cools naturally to room temperature in the air. Furthermore, the furnace atmosphere is either a slightly oxidizing atmosphere or protected by argon. Furthermore, in step S5, the walking beam continuous furnace is replaced with two box-type resistance furnaces. One box-type resistance furnace is set at 950°C and the other at 1080°C. The transfer time between the two furnaces is controlled within 3 minutes, and the water mist quenching station is set at a distance of ≤1 meter from the outlet of the high-temperature furnace. High strength and ultra-high plasticity are obtained by dissolving carbides and retaining subgrain boundary dislocations through two-stage continuous solution heat treatment and water mist quenching.
[0015] S6: Chromium-free passivation of the support; S61: The bracket treated in step S5 is completely immersed in the pickling tank at room temperature for 10-15 minutes to remove the heat-treated oxide scale. Furthermore, if the stent still has residual dark brown oxide scale after step S61, it can be acid-washed for 3-5 minutes. Furthermore, the solution in the pickling tank is 10% sulfuric acid + 5% hydrofluoric acid. The preparation method is as follows: first add tap water to the pickling tank to fill about 2 / 3 of the tank volume, then slowly add 98% concentrated sulfuric acid to a final concentration of 10%, and then slowly add 40% hydrofluoric acid to a final concentration of 5%. S62: Immerse the bracket in the first tap water rinsing tank, lift and shake it up and down 10 to 15 times to fully dilute and rinse away the residual acid on the surface of the bracket. Then transfer the bracket to the second tap water rinsing tank and repeat the up and down lifting and shaking cleaning. Furthermore, the total time for rinsing with tap water twice is 2-3 minutes; S63: Heat the passivation solution to 40~50℃ and keep it at a constant temperature. Immerse the drained support after washing in water completely into the passivation tank and soak for 15~20 minutes. Furthermore, the passivation solution formula is 5~8g / L citric acid + 30~50ml / L hydrogen peroxide + 0.5~1g / L cerium nitrate. The pH of the passivation solution is adjusted to 1.5~2.5 with ammonia. The preparation method is as follows: add deionized water to about 2 / 3 of the passivation tank volume; add citric acid at a concentration of 5~8g / L and stir until completely dissolved; add cerium nitrate at a concentration of 0.5~1g / L and stir until completely dissolved; then add 30% hydrogen peroxide at a concentration of 30~50ml / L and stir evenly; slowly add ammonia dropwise to adjust the pH of the passivation solution to 1.5~2.5. Furthermore, after treating 2-3 batches of stents with the passivation solution, add 3-5 ml / L of hydrogen peroxide according to the consumption to maintain an effective concentration; S64: Immerse the passivated support in deionized water, lift and shake it repeatedly and soak for 3-5 minutes. Take out the cleaned support, let it stand to drain for 2-3 minutes, and then dry it with hot air for 20-30 minutes to obtain the finished support. Furthermore, the conductivity of deionized water is ≤5μS / cm; Furthermore, the drying temperature is ≤80℃; By generating a cerium-rich oxide film through chromium-free passivation, hexavalent chromium is completely eliminated.
[0016] This invention achieves a triple superposition of grain refinement, second-phase dispersion strengthening, and subgrain boundary dislocation strengthening through rare earth ultra-low sulfur grain boundary purification, combined with mechanical vibration and forced air cooling for grain refinement, dual-stage continuous solid solution and water mist flexible quenching, and chromium-free cerium salt passivation. At the same time, the rare earth purified grain boundaries eliminate the early initiation source of plastic damage, achieving simultaneous improvement in strength and plasticity. The fracture mode is completely transformed from intergranular brittle fracture to micropore aggregated ductile fracture. Under accidental overload, it bends first and then fractures, providing a visible mechanical early warning signal for equipment inspection and preventing sudden disasters.
[0017] (1) Brinell hardness test: Environmental conditions: 25℃, 60%RH; Testing standards: GB / T 231.1-2018, GB / T 2100-2017; Testing equipment: Digital Brinell hardness tester; Test results: See Table 1; Table 1. Brinell hardness test results Brinell hardness (HBW 5 / 750) 153 155 152 153 (2) Tensile testing: Environmental conditions: 25℃, 60%RH; Testing standards: GB / T 228.1-2021, GB / T 2100-2017; Testing equipment: electronic universal testing machine, electronic extensometer; Test results: See Table 2; Table 2 Tensile Test Results result 585 231 64.0 Require ≥440 ≥175 ≥30 (3) Component analysis: Environmental conditions: 25℃, 60%RH; Testing standards: GB / T 11170-2008, GB / T 2100-2017; Test equipment: SPECTRO MAXx direct-reading spectrometer; Test results: See Table 3; Table 3 Component Analysis Results content 0.05 0.94 0.71 0.035 0.005 18.60 8.15 Require ≤0.07 ≤1.50 ≤1.50 ≤0.040 ≤0.030 18.00-20.00 8.00-11.00 (4) Metallographic structure analysis: Environmental conditions: 25℃, 60%RH; Testing standard: GB / T 13298-2015; Testing equipment: Metallurgical microscope; Test results: White austenitic matrix + black δ-ferrite, with dendritic distribution; Test image: see Figures 2-3 .
[0018] The present invention has been described in the above-described embodiments; however, these embodiments are merely examples for implementing the present invention. It must be noted that the disclosed embodiments do not limit the scope of the present invention. Conversely, any modifications and refinements made without departing from the spirit and scope of the present invention are within the scope of patent protection of the present invention.
Claims
1. An industrial method for preparing a high-strength, high-ductility cast austenitic stainless steel support, characterized in that: Includes the following steps: S1: AOD refining of molten steel and rare earth cored wire feeding modification treatment; S11: Melting scrap steel, ferrochrome, and ferronickel into molten steel in a medium-frequency induction furnace; S12: The molten steel is transferred to the AOD argon-oxygen refining furnace for blowing, and the argon-oxygen ratio is controlled to decarburize, desulfurize, and deoxidize the molten steel, thereby reducing the carbon content of the molten steel. S13: Use a wire feeder to feed a mixed rare earth cored wire of cerium (Ce) and lanthanum (La) into the depth of the molten steel at a set speed; S14: After feeding the wire, let it stand for several minutes to allow the rare earth elements to react fully, and then remove the residue; S2: Prepare the heat storage mold shell; S21: Topcoat application and drying; S22: Back coating and drying; S23: Sealing layer and drying; S24: Dewaxing and roasting; S3: Molten steel is poured through mechanical resonance vibration and then solidified by forced air cooling to form a casting; S31: With the pouring cup of the baked high-temperature mold shell facing vertically upwards, quickly hoist it onto the pneumatic / eccentric wheel mechanical vibration table and fix it securely; S32: Slowly tilt the ladle to allow the refined molten steel from step S1 to flow into the mold shell in a spiral shape along the inner wall of the pouring cup, with the pouring time controlled within the set time. S33: Immediately after the molten steel is poured, start the vibrating table and set the frequency and amplitude; S34: After casting, the temperature of the molten steel decreases and it enters the solid-liquid two-phase region where δ ferrite begins to precipitate. Mechanical shearing force is used to break up the growing primary δ dendrites, forming a large number of free crystal nuclei. Vibration continues for several minutes until the outer shell is completely solidified. S35: After casting is completed, the array-type axial flow fan around the mold shell is turned on to provide high-flow forced air convection cooling to the surface of the mold shell until the surface temperature of the mold shell drops below 600℃. S36: When the outer shell of the mold is completely solidified and the reading of the vibrating table ammeter drops significantly, stop the vibrating table. After stopping the machine, loosen the clamping device and transfer the mold along with the vibrating table surface to the cooling rack for continued natural air cooling or auxiliary air cooling to below 200°C. S4: Cleaning, cutting and grinding castings; S41: After the casting has cooled naturally to below 200°C in the mold shell, mechanical vibration or water blasting is performed to remove the outer mullite shell layer. S42: Use an oxyacetylene flame cutter or band saw to separate the support block from the gating system; S43: Use an angle grinder or shot blasting machine to remove residual shell, flash, and oxide scale from the surface of the bracket to expose the metal. S5: The bracket undergoes two-stage continuous solution heat treatment and water mist quenching; S51: After cleaning, cutting and grinding the bracket in step S4, blow the surface and inner cavity with compressed air to remove residual molding sand, iron filings and oxide scale, and wipe the oil stains on the surface of the casting with industrial alcohol or acetone. S52: Place the cleaned supports evenly on the bottom bricks at the feed end of the walking beam furnace, leaving gaps between the castings to ensure uniform hot air circulation; S53: Start the stepper beam drive system and feed the supports into the furnace zone one batch by batch according to the set cycle. The furnace temperature is controlled at 950±5℃ and held for 2±0.5 hours to fully dissolve the grain boundary carbides and uniformly alloy the elements. S54: The walking beam pushes the casting to the transition section, and the roller conveyor is used for rapid transfer, so that the casting can enter the furnace zone 2 as soon as possible from zone 1. S55: The support enters the second zone of the furnace, and the furnace temperature is controlled at 1080±5℃ for 15±1 minutes. S56: The walking beam quickly sends the support after the heat preservation in Zone 2 of the furnace into the quenching zone. After the support comes out of the furnace, it immediately enters the high-pressure water mist and compressed air mixed spray zone until the surface temperature of the casting drops below 200°C. S57: After the bracket leaves the spray zone, it enters the natural air drying section or the compressed air blowing section to blow away the residual water stains on the surface. The bracket continues to move forward with the roller conveyor and cools naturally to room temperature in the air. S6: Chromium-free passivation of the support; S61: The bracket treated in step S5 is completely immersed in the pickling tank at room temperature for several minutes to remove the heat-treated oxide scale. S62: Immerse the bracket in the first tap water rinsing tank, lift and shake it up and down to fully dilute and rinse away the acid residue on the surface of the bracket, then transfer the bracket into the second tap water rinsing tank and repeat the up and down lifting and shaking cleaning. S63: Heat the passivation solution to 40~50℃ and keep it at a constant temperature. Immerse the drained support after washing in water completely into the passivation tank and soak for several minutes. The passivation solution is formulated as follows: 5~8g / L citric acid + 30~50ml / L hydrogen peroxide + 0.5~1g / L cerium nitrate. The pH of the passivation solution is adjusted to 1.5~2.5 with ammonia. S64: Immerse the passivated support in deionized water, lift and shake it several times and soak it for several minutes. Then, lift the cleaned support out, let it stand to drain, and then dry it with hot air to obtain the finished support.
2. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: In step S12, the blowing process includes the following sub-steps: S121: In the AOD argon-oxygen refining furnace, O2:Ar = 3:1~4:1 is blown in, with oxygen as the main component. High-pressure oxygen is blown in simultaneously through the top and side lances. The temperature of the molten steel rises to 1650℃~1700℃. The carbon content is high, and oxygen preferentially reacts with carbon. CO is burned to produce CO2, and a large amount of brown smoke is produced at the furnace mouth. The exhaust gas analyzer shows that the CO content in the exhaust gas drops sharply, and when the temperature of the molten steel reaches its peak, the carbon content drops to 0.40%~0.50%. S122: Gradually adjust the side-blown gas ratio to O2:Ar=1:1~1:2, significantly increase the argon flow rate. The large injection of argon forms a large number of tiny bubbles inside the molten steel. When the bubbles are first generated, there is no CO. The bubbles compete for dissolved carbon and oxygen in the molten steel, promoting the reaction to move to the right. The temperature of the molten steel is maintained at 1700℃~1720℃. The exhaust gas analyzer shows that the CO partial pressure continues to decrease and the carbon content exceeds the critical point of 0.10%. S123: Switch the argon-oxygen ratio to O2:Ar=1:3~1:4, with argon as the main gas and oxygen only in trace amounts. The large amount of argon gas strongly stirs the molten steel, generating a vacuum suction effect. This draws in the trace amounts of carbon and oxygen remaining in the molten steel, which combine to form CO and are then expelled. At the same time, Cr2O3 in the slag is also reduced by the carbon in the molten steel: Cr2O3 + 3C → 2Cr + 3CO, further squeezing out the residual carbon. The temperature of the molten steel is maintained at 1720℃~1750℃, and the high argon gas stirring is maintained for 10~15 minutes, during which the carbon content is stably reduced to 0.03%~0.05%. S124: In steps S122-S123, ferrosilicon or aluminum particles are added in batches. The exothermic oxidation Si+O2→SiO2 is used to pull the temperature of the molten steel back to above 1700℃, providing energy for the decarburization reaction. S125: In steps S121-S123, active lime is added to the furnace in batches to control the slag basicity at 2.0~2.
5. The high basicity slag adsorbs the SiO2 generated by decarburization and absorbs the sulfur in the molten steel.
3. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: In step S1, the temperature in the medium-frequency induction furnace is ≥1600℃; the wire feeding amount is 0.15%~0.25% of the weight of the molten steel; the wire feeding speed is 2.5~3.0 m / s; the wire is left to stand for 5~8 minutes after feeding; the tapping temperature of the molten steel after step S1 is 1580±10℃.
4. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: Step S21 includes the following sub-steps: S211: Preparation of surface layer slurry; Using silica sol as a binder, zircon powder is slowly added to silica sol at a ratio of zircon powder: silica sol = 3.2:1~4.0:
1. At the same time, 0.2% of the coating mass of wetting agent and 0.2% of defoamer are added. After stirring continuously for 2~3 hours, the slurry density is 2.7~2.8 g / mL and the flow cup viscosity is 32±1 seconds. Furthermore, the wetting agent is polyoxyethylene alkyl ether, and the defoamer is n-octanol; S212: Immerse the wax model assembly in the surface slurry prepared in step S211; S213: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up the surface. S214: Send the module coated with slurry into the sand-spraying machine and evenly sprinkle 80~120 mesh zircon sand on it; S215: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 50%~70%, dry for 14 hours; S216: Repeat steps S212-S215, applying two coats of topcoat.
5. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: Step S22 includes the following sub-steps: S221: Preparation of backing slurry; Using silica sol as a binder, 200-mesh mullite powder was added, with a mullite powder: silica sol ratio of 1.8:1 to 1.9:
1. The mixture was stirred for 2 to 3 hours and set aside. The slurry density was 1.81 to 1.83 g / mL and the viscosity was 13 ± 1 second. S222: Immerse the module in pure silica sol for 2-3 seconds and then remove it to wet the surface of the previous layer. S223: Immerse the wax mold assembly in the backing slurry prepared in step S221; S224: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up the surface. S225: The module coated with slurry is sent into the sand-spraying machine and evenly sprinkled with 16~30 mesh mullite sand; S226: Transfer to a constant temperature and humidity drying chamber, temperature 22~24℃, humidity 35%~50%, dry for 12~18 hours; S227: Repeat steps S223-S227, applying 3-4 layers of back coat.
6. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: Step S23 includes the following sub-steps: S231: The sealant grout has the same formula as the backing grout. S232: Immerse the wax mold assembly into the sealing slurry prepared in step S231; S233: Remove the module, slowly rotate and tilt it to allow excess paste to drip off naturally, making the surface coating even. For small and complex areas where paste was not applied, use a small brush to apply paste to touch up. S234: Transfer to a constant temperature and humidity drying chamber, with conditions of 22~24℃ and 35%~50% humidity, for 8~12 hours of drying.
7. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: Step S24 includes the following sub-steps: S241: Before dewaxing, perform a pressure test on the dewaxing kettle and preheat it 1-2 times. Place the mold pouring cup upside down on the dewaxing trolley and quickly feed it into the dewaxing kettle. Immediately close the machine door, open the steam valve, and quickly raise the pressure to 0.6-0.75MPa. Hold the pressure at 0.6-0.75MPa and 135℃-160℃ for 6-15 minutes. After the holding time is up, close the steam valve and slowly release the steam. After the pressure gauge returns to zero, open the kettle door and pull out the mold shell. S242: Place the dewaxed mold shell into the firing furnace, start the firing furnace, and heat it to 1000~1050℃ according to the set program. The heating rate is controlled at 5~8℃ / min to avoid thermal shock cracking of the mold shell due to excessive heating. Hold it at 1000~1050℃ for 1.5~2 hours. After the holding time is over, open the furnace door and take out the mold shell. After firing, keep the temperature of the mold shell at 700~800℃.
8. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: In step S3, the wind speed of the high-flow forced air convection cooling is ≥10m / s; the color of the mold shell surface changes from bright red to dark red when viewed visually, then the outer shell of the mold shell is completely solidified; the reading of the vibration table ammeter drops significantly, indicating that the molten steel has solidified and no longer consumes vibration energy.
9. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: In step S5, the compressed air pressure is ≥0.6MPa; the cycle is set to 5~10 minutes / step cycle; the water mist pressure in the high-pressure water mist and compressed air mixed spray zone is 0.6~0.8MPa, the air pressure is 0.5~0.6MPa, and the cooling rate is ≥50℃ / s; the furnace atmosphere is a slightly oxidizing atmosphere or argon protection; in step S5, the walking beam continuous furnace is replaced with two box-type resistance furnaces, one set to 950℃ and the other set to 1080℃, the transfer time between the two furnaces is controlled within 3 minutes, and the water mist quenching station is set at ≤1 meter away from the high-temperature furnace outlet.
10. The industrial manufacturing method of the high-strength, high-ductility cast austenitic stainless steel bracket as described in claim 1, characterized in that: In step S6, if the stent still has residual dark brown oxide scale after step S61, it can be acid-washed for 3-5 minutes; the solution in the acid-washing tank is 10% sulfuric acid + 5% hydrofluoric acid; the total time for rinsing with tap water twice is 2-3 minutes; after continuously treating 2-3 batches of stents with passivation solution, hydrogen peroxide is added according to the consumption to maintain an effective concentration; the conductivity of deionized water is ≤5μS / cm; the drying temperature is ≤80℃.
Citation Information
Patent Citations
Precision casting process of thin-wall complex casting for high-horsepower engine
CN113333677A
Silica sol precision casting process
CN120533008A